Diisodecyl phthalate aggravates thyroid autoimmune injury in thyroglobulin-sensitized rats via endoplasmic reticulum stress-mediated apoptosis and Th17/Treg dysregulation - Zixin Tian; Jianwei Gao; Zhenjie Lu; Keyi Chen; Wanjia Lv; Mei Ye; Yajun Wang; Yanling Sun; Xu Yang; Ping Ma; Yang Wu (Food and Chemical Toxicology, 2026)

PFAS penetrate the bone marrow microenvironment and alter immunometabolic homeostasis - Sijia Gu; Ji Ma; Xiangying Sun; Keyi Li; Mingzhu Wu; Yumeng Shi; Miao Xu; Hongkai Zhu; Hongwen Sun (Environmental Pollution, 2026)

Acesulfame K, not as sweet as you think: Insights into its physiological and biochemical side-effects on rice growth and development - Xiaoyan Ma; Keyi Xu; Liqin Zhong; Hailong Xu; Qixian Xu; Yali Song; Jing Deng; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2026)

Ultra-fast degradation of sulfonamides by Fe/Cu-LDH functionalized biochar activated peroxymonosulfate: Interfacial catalysis driven multiple reactive oxygen species - Yongfei Ma; Keyi Li; Feifei Zhang; Zhaojun Nie; Shiyu Qin; Haiyang Liu; Yupeng Zhang; Jiayang Xu; Zulin Zhang; Peng Zhao; Hongen Liu (Chemical Engineering Journal, 2026)

A transcriptome dataset for early phenotypic sex differentiation in the mud crab Scylla paramamosain - Haolin Yang; Zhiqiang Liu; Chunyan Ma; Wei Wang; Lingbo Ma; Keyi Ma (Frontiers in Marine Science, 2026)

High-performance and recyclable HKUST-1-derived CuxO/Steel electrode for electrocatalytic dechlorination of trichloroacetic acid - Mengyuan Xu; Yunhua Lv; Keyi Xu; Liqin Zhong; Kunming Wei; Xiaoyan Ma; Su Jiang; Jing Deng; Hanxuan Zeng; Qingsong Li; Stefanos Giannakis; Andrea M. Dietrich (Journal of Cleaner Production, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Comparative transcriptomic analysis of the megalopa metamorphosis development reveals candidate genes associated with developmental remodeling and putative brachyurization in the mud crab Scylla paramamosain - Keyi Ma; Likun Xu; Zhiqiang Liu; Xueyang Wang; Lingbo Ma; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2026)

Pyrolysis-derived recovered glass fiber-engineered ultrafiltration membrane for dyeing wastewater treatment - Fengzhi Guo; Haolun Wang; Fan Shao; Jinzhi Jiang; Guorui Li; Xinmeng Ma; Haoran Ma; Keyi Li; Lu Gong; Yue Ma; Changtao Yue (Chemical Engineering Journal, 2026)

Vertical distribution pattern, preferred life strategies and environmental response of prokaryotic microbiome in the eastern tropical indian ocean - Jinfeng Wang; Wenbin Zhao; Shaodong Zhu; Keyi Huang; Yulin Zhang; Haojin Cheng; Qin Ma; Derui Song; Jiwen Liu; Xiao-Hua Zhang; Xiaolei Wang (Marine Environmental Research, 2026)

Pennsylvanian fusulinids from the Narao section, southern Guizhou, South China and their biostratigraphic significance for the Bashkirian-Moscovian and Moscovian-Kasimovian boundaries - Xinyi Ma; Keyi Hu; Yukun Shi; Xiangdong Wang (Journal of Asian Earth Sciences, 2026)

A plasticity-aware machine learning framework for genomic prediction and resource-efficient wheat breeding under multi-environment conditions - Lei Li; Cong Zhao; Huihui Li; Xi Tian; Jindong Liu; Duoxia Wang; Keyi Wang; Shuaipeng Fei; Guoliang Wan; Jianqi Zeng; Yachao Dong; Jixin Li; et al. (Computers and Electronics in Agriculture, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

Investigation of SNPs at NKCC Gene of Scylla paramamosain to Unveil the Low-Salinity Tolerance Phenotype - Chunyan Yin; Yanqing Ma; Zhiqiang Liu; Xueyang Wang; Keyi Ma; Wei Wang; Chunyan Ma; Fengying Zhang (Fishes, 2026)
The Na+/K+/2Cl− cotransporter (NKCC) gene encodes a critical membrane transporter involved in cellular ion homeostasis and plays a pivotal role in osmoregulation and salinity adaptation in aquatic organisms. This study identified and validated SNP markers in the NKCC gene associated with low-salinity tolerance in Scylla paramamosain. Four SNPs (g.196C>A, g.8374T>A, g.8385T>A and g.91143T>A) were screened and genotyped in low-salinity tolerant and intolerant groups. Association analysis revealed that mutant genotypes at all four sites were significantly enriched in the tolerant group (p

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

Imidazolium salt-functionalized Cu2O@SiO2 catalysts for integrated CO2 capture and electroreduction to multi-carbon products in acidic electrolytes - Hui Zhang; Shanshan Lou; Fan Yang; Keyi Fan; Zhengxin Gu; Wangbo Li; Yihe Chen; Yizhen Gan; Lushan Ma; Guoliang Wang; Hui Yang (Chemical Engineering Journal, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

Early estimation of glutelin to gliadin ratio in wheat grain using high-dimensional and hyperspectral reflectance - Junjie Ma; Keyi Wang; Bangyou Zheng; Yinlong Xu; Yong He (Computers and Electronics in Agriculture, 2024)

Preparation, separation, and identification of antioxidant peptides from protein hydrolysate of Polygonatum cyrtonema Hua - Yanyan Zhang; Shengjun Ma; Haixia Li; Peizi Liu; Keyi Chen; Wei Cai (Food Bioscience, 2024)

The mechanistic insights and therapeutic implications of sheepskin collagen peptide as a novel anti-photoaging agent - Baifeng Fu; Keyi Zhou; Hui Yao; Ximing Yang; Xiaoyu Ma; Qi Yang; Shuzhen Cheng; Ming Du (Food Bioscience, 2024)

Effects of four diets on the metabolism of megalopa metamorphosis of the mud crab, Scylla paramamosain - Keyi Ma; Zhiqiang Liu; Guangde Qiao; Lingbo Ma; Fengying Zhang; Ming Zhao; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2023)
Dietary intake is an essential source of energy and nutrients, and plays an irreplaceable role in the breeding of S. paramamosain seedlings. In this study, live Artemia nauplii (LA), compound feeds (CF), frozen copepods (FC) and frozen adult Artemia (FA) were utilized as feed during the megalopa stage. To determine the impact that diet has on the metabolism of crablets that underwent metamorphosis from the megalopa stage, analyses of both metabolomics and fatty acid content were conducted. In the LC-MS-based metabolomics analysis, a total of 104, 205 and 83 significantly different metabolites (SDMs) were identified after being fed with FC, FA, and CF, respectively, as compared to the LA group. Furthermore, significant differences in KEGG compounds among the three comparisons exhibited similarity and were mainly associated with categories such as “Lipids”, “Hormones and transmitters”, and “Peptides”. The fatty acid content analysis indicated that the ΣMUFA was significantly higher in the LA and CF groups compared to the other two groups. In contrast, the highest level of ΣPUFA was found in the LA group. In addition, the CF group showed significantly higher expression levels of the fatty acid synthesis genes, FAS and ACC . Conversely, the expression level of the fatty acid decomposition-related gene CPT1 was the highest in the LA group. In comparison with the FA group, the expression level of FABP3 was significantly decreased in the LA and CF groups. In summary, there were significant differences observed in the metabolic profiles of crablets that metamorphosed from the megalopa under different diets. Our experimental results suggested that LA is more advantageous in the cultivation of the S. paramamosain megalopa compared to the other three diets. While it remains a diet that cannot be entirely substituted at present, LA has the potential to improve the culture performance of the S. paramamosain megalopa. The current study could provide valuable data into the development of artificial diets necessary for the future of the mud crab seedling breeding industry.

Improving quantification of methane point source emissions from imaging spectroscopy - Zhipeng Pei; Ge Han; Huiqin Mao; Cuihong Chen; Tianqi Shi; Keyi Yang; Xin Ma; Wei Gong (Remote Sensing of Environment, 2023)

Suppression of ETI by PTI priming to balance plant growth and defense through an MPK3/MPK6-WRKYs-PP2Cs module - Dacheng Wang; Lirong Wei; Ting Liu; Jinbiao Ma; Keyi Huang; Huimin Guo; Yufen Huang; Lei Zhang; Jing Zhao; Kenichi Tsuda; Yiming Wang (Molecular Plant, 2023)

Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.

Impact of Titanium Dioxide-Graphene Oxide (TiO2-GO) Composite Nanoparticle on the Juveniles of the Giant River Prawn, Macrobrachium rosenbergii: Physio-Biochemistry and Transcriptional Response - Ziqi Guo; Jiabao Zuo; Jianbin Feng; Jiale Li; Shupeng Zhang; Keyi Ma (Marine Biotechnology, 2023)

Short-term effects of ambient particulate matter (PM1, PM2.5 and PM10) on influenza-like illness in Guangzhou, China - Jianyun Lu; Keyi Wu; Xiaowei Ma; Jing Wei; Zelin Yuan; Zhiwei Huang; Weidong Fan; Qi Zhong; Yining Huang; Xianbo Wu (International Journal of Hygiene and Environmental Health, 2023)

Response of bacterial communities to shrub encroachment and forage planting in alpine grassland of the Qinghai-Tibetan Plateau - Wenming Ma; Keyi Ding; Song Bai; Changting Wang; Tenzing Droma (Ecological Engineering, 2023)

Effects of titanium dioxide (TiO2)/activated carbon (AC) nanoparticle on the growth and immunity of the giant freshwater prawn, Macrobrachium rosenbergii: potential toxicological risks to the aquatic crustaceans - Ziqi Guo; Jiabao Zuo; Xue Liu; Jinhua Gong; Keyi Ma; Jianbin Feng; Jiale Li; Shupeng Zhang; Gaofeng Qiu (Environmental Science and Pollution Research, 2022)

RNA-seq Provides Novel Insights into Response to Acute Salinity Stress in Oriental River Prawn Macrobrachium nipponense - Yaoran Fan; Jianbin Feng; Nan Xie; Feiyue Ling; Zefei Wang; Keyi Ma; Xueming Hua; Jiale Li (Marine Biotechnology, 2022)

Cloning and expression analysis of juvenile hormone epoxide hydrolase-like ( EsJHEH-like ) from Eriocheir sinensis , and its potential roles in methyl farnesoate metabolism - Tiantian Chen; Yingzhu Diao; Ruihan Xu; Na Sheng; Fan Liu; Qiming Xie; Shiping Su; Keyi Ma; Xilei Li (Invertebrate Reproduction & Development, 2022)

Dihydromyricetin Ameliorates 3NP-induced Behavioral Deficits and Striatal Injury in Rats - Shuhua Mu; Youlan Li; Bingbing Liu; Weiping Wang; Si Chen; Jiajia Wu; Lisi OuYang; Yaxi Zhu; Keyi Li; Mali Zhan; Zongwei Liu; Yu Jia; et al. (Journal of Molecular Neuroscience, 2016)

Stability of soil organic carbon and potential carbon sequestration at eroding and deposition sites - Wenming Ma; Zhongwu Li; Keyi Ding; Bin Huang; Xiaodong Nie; Yinmei Lu; Haibin Xiao; Guangming Zeng (Journal of Soils and Sediments, 2016)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)

High level expression of a truncated β-mannanase from alkaliphilic Bacillus sp. N16-5 in Kluyveromyces cicerisporus - Xian Pan; Jungang Zhou; Ai Tian; Keyi Le; Hanying Yuan; Yanfen Xue; Yanhe Ma; Hong Lu (Biotechnology Letters, 2011)